Anti-aging high-grade waterproof asphalt and preparation method thereof
By using specific raw material systems and treatment steps, high-grade anti-aging waterproof asphalt is prepared, which solves the problems of environmental pollution and reduced anti-aging performance caused by volatile organic compounds in traditional waterproof rolls, and achieves better anti-aging and low-temperature performance.
Patent Information
- Application Number
- CN202311432063.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The waste engine oil and rubber oil used in the production process of traditional asphalt-based waterproof coils contain volatile organic compounds, resulting in environmental pollution and reduced anti-aging performance of waterproof materials.
A raw material system including matrix asphalt, catalytic oil slurry, furfural extraction oil, converter, adsorbent and filler is used to prepare anti-aging high-grade waterproof asphalt through specific mixing and processing steps. The specific steps include using rejoining 70# asphalt, catalytic cracked oil slurry and furfural extracting oil, and adding siligotungstic acid as a converter, bamboo wood nanofiber aerogel as an adsorbent and activated acetaminite as a filler, and undergoing high-speed shearing and sonication.
Through this method, the volatility of light components when asphalt is heated is significantly reduced, the anti-aging and low-temperature properties of the waterproof material are improved, the environment is protected, and the manufacturing process is simplified.
Smart Images

Figure BDA0004523940810000071 
Figure BDA0004523940810000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waterproof materials, and specifically relates to an anti-aging high-grade waterproof asphalt, especially an anti-aging high-grade waterproof asphalt, and further discloses a preparation method thereof. Background Art
[0002] Since the mid-1980s, China has begun to develop modified asphalt technology and waterproofing membrane production, and has been widely used in various fields. After decades of development, SBS modified asphalt waterproofing membrane has become the most widely used new building waterproofing material in China due to its excellent physical, chemical properties and construction application performance. At present, my country's SBS modified asphalt waterproofing membrane production capacity has jumped to the first place in the world, with annual sales reaching several billion square meters. Among them, asphalt, as an important production raw material, plays a vital role in the performance of waterproofing membranes.
[0003] In the production process of traditional asphalt-based waterproofing membranes, petroleum asphalt is mainly mixed with waste engine oil or rubber oil in a certain proportion to prepare waterproofing membrane asphalt, and the waterproofing membrane asphalt is produced by the "pre-mixing and pre-use" method. The disadvantage of this process is that the volatile organic matter contained in waste engine oil and rubber oil is easy to volatilize during the production process of polymer-modified asphalt, which will pollute the environment and reduce the anti-aging performance of waterproof materials. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to provide an anti-aging high-grade waterproof asphalt, which has good anti-aging performance and good low-temperature performance;
[0005] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned anti-aging high-grade waterproof asphalt.
[0006] In order to solve the above technical problems, the present invention discloses an anti-aging high-grade waterproof asphalt, which comprises the following raw materials in parts by weight: 70-80 parts by weight of base asphalt, 6-10 parts by weight of catalytic oil slurry, 10-18 parts by weight of furfural extracted oil, 0.1-0.25 parts by weight of conversion agent, 1-3 parts by weight of filler, and 0.03-0.05 parts by weight of adsorbent.
[0007] Specifically, the anti-aging high-grade waterproof asphalt, the furfural extracted oil includes one or a mixture of two of furfural extracted oil minus three lines and furfural extracted oil minus four lines;
[0008] Preferably, the aromatic content in the furfural extracted oil is ≥40%.
[0009] Specifically, the anti-aging high-grade waterproof asphalt, the adsorbent includes bamboo wood nanofiber aerogel;
[0010] Preferably, the preparation method of the bamboo wood nanofiber aerogel comprises the steps of taking bamboo wood cellulose nanofibers and placing them in water and ethanol solutions for immersion, and the step of pressurizing and heating the bamboo wood nanofibers;
[0011] Preferably, the impregnation step comprises the steps of adding water to the bamboo wood cellulose nanofibers for immersion for 20-30 hours, and then taking out the bamboo wood cellulose nanofibers and continuing to add ethanol solution for immersion for 20-30 hours;
[0012] More preferably, the impregnation step comprises the steps of adding water to the bamboo wood cellulose nanofibers and impregnating them for 24 hours, and then taking out the bamboo wood cellulose nanofibers and continuing to add ethanol solution to impregnate them for 24 hours;
[0013] Preferably, the pressure heating treatment step is performed for 6-10 hours, more preferably 8 hours.
[0014] Specifically, the anti-aging high-grade waterproof asphalt, the filler includes activated palygorskite;
[0015] Preferably, the method for preparing the activated palygorskite comprises the steps of adding the palygorskite to dilute hydrochloric acid and mixing, and treating the palygorskite at 50-80° C.; the preferred treatment temperature is 60° C.;
[0016] Preferably, the mass concentration of the dilute hydrochloric acid is 1%-2%;
[0017] Preferably, the mass ratio of the palygorskite to the dilute hydrochloric acid is 1:2-4 g / mL; the preferred mass ratio is 1:3 g / mL;
[0018] Preferably, the treatment time is 40-80 min; preferably, the treatment time is 60 min;
[0019] Preferably, the method further comprises the steps of washing and drying the treated activated palygorskite.
[0020] Specifically, the anti-aging high-grade waterproof asphalt, the base asphalt includes heavy-duty 70# asphalt.
[0021] Specifically, the anti-aging high-grade waterproof asphalt, the aromatic content of the catalytic cracking oil slurry is 40%-48%.
[0022] Specifically, the anti-aging high-grade waterproof asphalt, the conversion agent includes silicotungstic acid.
[0023] The present invention also discloses a method for preparing the anti-aging high-grade waterproof asphalt, comprising the steps of mixing selected amounts of the base asphalt, catalytic oil slurry, furfural extracted oil, conversion agent, absorbent and filler;
[0024] Preferably, the temperature of the mixing step is 120°C-130°C, preferably the mixing temperature is 125°C.
[0025] Specifically, the method for preparing the anti-aging high-grade waterproof asphalt comprises the following steps:
[0026] (1) heating a selected amount of the base asphalt to 120° C.-130° C.;
[0027] (2) continuing to add the selected amount of the catalytic oil slurry and furfural extracted oil, and performing high-speed shearing at a speed of 1000-1500 r / min for 30-40 min; preferably performing high-speed shearing at a speed of 1200 r / min for 35 min;
[0028] (3) continuing to add the selected amount of the conversion agent and absorbent, and continuing shearing for 20-40 minutes, and then continuing shearing under ultrasonic conditions for 0.5-1 hour;
[0029] (4) Continue to add the selected amount of the filler and continue shearing for 20-40 minutes.
[0030] Specifically, in the method for preparing the anti-aging high-grade waterproof asphalt, in the step (3), the power of the ultrasonic step is 4-8W, preferably 6W, and the ultrasonic time is 0.5-1h.
[0031] The anti-aging high-grade waterproof asphalt of the present invention uses heavy traffic asphalt, oil slurry and furfural extracted oil as basic raw materials. By adding a selected conversion agent, adsorbent and filler raw material system, the volatilization of light components when the asphalt is heated can be greatly reduced. The various components work together to improve the anti-aging performance of the waterproof material, and a high-grade waterproof asphalt with better anti-aging performance is prepared.
[0032] The anti-aging high-grade waterproof asphalt of the present invention is prepared by using catalytic cracking oil slurry and furfural extracted oil as raw materials. Since the catalytic cracking oil slurry and furfural extracted oil contain more saturated components and aromatic components, it is beneficial to the swelling of SBS in the process of preparing the coiled material.
[0033] The anti-aging high-grade waterproof asphalt of the present invention is prepared by adding silicotungstic acid as a conversion agent. The presence of silicotungstic acid converts aromatic components into high molecular weight substances during heating, thereby reducing the volatilization of harmful substances and protecting the environment.
[0034] The anti-aging high-grade waterproof asphalt of the present invention uses palygorskite as a filler. As a natural mineral microfiber, a large number of palygorskite fibers form a reinforcement network, which is intertwined with the spatial network of SBS, reducing the volatilization of saturated components with lower molecular weight in the asphalt, improving the anti-aging performance of the asphalt, and palygorskite has a large specific surface area and a special layered chain structure, so that it has a large specific surface contact area with the asphalt, improving the high and low temperature performance of the asphalt. And after palygorskite is acidified, it can coat the light component, reducing the volatilization of the light component, protecting the environment and improving the low temperature performance of the asphalt.
[0035] The anti-aging high-grade waterproof asphalt of the present invention adopts bamboo wood nanofiber aerogel as an adsorbent. The aerogel reacts during the preparation process to have a special fiber frame structure, which can adsorb organic light components volatilized during the preparation process, reduce the volatilization of light components, protect the environment, improve the anti-aging performance of the waterproof membrane, and improve the low-temperature performance of the membrane.
[0036] The method for preparing the anti-aging high-grade waterproof asphalt of the present invention adopts an ultrasonic treatment method during the mixing process, which improves the dispersibility of the absorbent and the converter, and the performance of the prepared high-grade waterproof asphalt is improved. It has the advantage of a simple and easy manufacturing process. Not only does the product have excellent anti-aging performance, but it also shortens the process flow for waterproof membrane manufacturers and greatly improves economic feasibility. It can be widely used in the production of elastomer / plastomer modified asphalt, self-adhesive polymer modified asphalt, pre-paved / wet-paved and modified asphalt waterproof membranes for roads and bridges. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention.
[0038] In the following embodiments of the present invention, the filler is activated palygorskite, and the preparation method of the activated palygorskite comprises: mixing palygorskite with 2% hydrochloric acid by mass at a solid-liquid ratio of 1:3, treating at 60° C. for 60 min, washing with water, and drying.
[0039] In the following embodiment of the present invention, the adsorbent is bamboo wood nanofiber aerogel, and the preparation method of the bamboo wood nanofiber aerogel comprises: soaking the bamboo wood cellulose nanofiber in water for 24 hours, then taking out the bamboo wood nanofiber and continuing to soak it in an ethanol solution for 24 hours, and after taking it out, heating the nanofiber in a pressurized oven for 8 hours to obtain the desired bamboo wood nanofiber aerogel.
[0040] In the following Examples 1-3 and Comparative Examples 1-6 of the present invention, the properties and parameters of the same raw material components are the same.
[0041] Example 1
[0042] Heat 70 parts of base asphalt to 125°C, add 6 parts of catalytic oil slurry and 10 parts of furfural extraction oil, mix, and perform high-speed shearing at a speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, add 0.1 parts of silicotungstic acid and 0.03 parts of bamboo wood nanofiber aerogel, continue to shear for 30 minutes, and then continue to shear under ultrasonic conditions (power 6W) for 0.5h, continue to maintain the temperature, add 1 part of activated palygorskite and continue to shear for 30 minutes.
[0043] Example 2
[0044] Heat 75 parts of base asphalt to 125°C, add 8 parts of catalytic oil slurry and 14 parts of furfural extraction oil, mix, and perform high-speed shearing at a speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, add 0.15 parts of silicotungstic acid and 0.04 parts of bamboo wood nanofiber aerogel, continue to shear for 30 minutes, and then continue to shear under ultrasonic conditions (power 6W) for 0.5h, continue to maintain the temperature, add 2 parts of activated palygorskite and continue to shear for 30 minutes.
[0045] Example 3
[0046] Heat 80 parts of base asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, and perform high-speed shearing at a speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and 0.05 parts of bamboo wood nanofiber aerogel, continue to shear for 30 minutes, and then continue to shear under ultrasonic conditions (power 6W) for 0.5h, continue to maintain the temperature, add 3 parts of activated palygorskite and continue to shear for 30 minutes.
[0047] Comparative Example 1
[0048] Heat 80 parts of base asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, and high-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and shear for 30 minutes, then continue to shear for 0.5 hours under ultrasonic conditions (power 6W), finally add 3 parts of activated palygorskite at this temperature and continue to shear for 30 minutes.
[0049] Comparative Example 2
[0050] Heat 80 parts of base asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, and high-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, and then continue to shear for 0.5h under ultrasonic conditions (6W).
[0051] Comparative Example 3
[0052] Heat 80 parts of base asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, and high-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, then continue to shear for 0.5h under ultrasonic (6W) conditions, and finally add 3 parts of activated palygorskite at this temperature and shear for 30 minutes.
[0053] Comparative Example 4
[0054] Heat 80 parts of base asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, high-speed shear at 1200r / min for 35min, and then continue shearing for 0.5h under ultrasonic (6W) conditions to obtain the product.
[0055] Comparative Example 5
[0056] Heat 80 parts of base asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, and high-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, finally add 3 parts of activated palygorskite at this temperature and shear for 30 minutes.
[0057] Comparative Example 6
[0058] Heat 80 parts of base asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, and high-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.25 parts of phosphomolybdic acid and 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, then continue to shear for 0.5h under ultrasonic conditions (6W), and finally add 3 parts of activated palygorskite at this temperature and shear for 30 minutes.
[0059] Experimental example
[0060] The properties of the high-grade waterproof asphalt prepared in Examples 1-3 above were measured and shown in Table 1 below.
[0061] Table 1 Performance of high-grade waterproof asphalt in Examples 1-3
[0062]
[0063] The properties of the high-grade waterproof asphalt prepared in the above comparative examples 1-6 were respectively measured and shown in Table 2 below.
[0064] Table 2 Performance of high-grade waterproof asphalt in comparative examples 1-6
[0065]
[0066] It can be seen from the data in Tables 1 and 2 above that the high-grade waterproof asphalt material prepared using the raw material system of the present invention has good application performance in all aspects, and the softening point increment of the prepared high-grade waterproof asphalt before and after aging is small, and the evaporation loss is small, indicating that the high-grade waterproof asphalt prepared using the present invention has good anti-aging performance.
[0067] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. An anti-aging high-grade waterproof asphalt, characterized in that: The asphalt comprises the following raw materials in parts by weight: 70-80 parts by weight of base asphalt, 6-10 parts by weight of catalytic oil slurry, 10-18 parts by weight of furfural extracted oil, 0.1-0.25 parts by weight of conversion agent, 1-3 parts by weight of filler, and 0.03-0.05 parts by weight of adsorbent.
2. The anti-aging high-grade waterproof asphalt according to claim 1 is characterized in that: The furfural extracted oil comprises one or a mixture of three-line furfural extracted oil and four-line furfural extracted oil; Preferably, the aromatic content in the furfural extracted oil is ≥40%.
3. The anti-aging high-grade waterproof asphalt according to claim 1 or 2, characterized in that: The adsorbent includes bamboo wood nanofiber aerogel; Preferably, the preparation method of the bamboo wood nanofiber aerogel comprises the steps of taking bamboo wood cellulose nanofibers and placing them in water and ethanol solutions for immersion, and the step of pressurizing and heating the bamboo wood nanofibers; Preferably, the impregnation step comprises the steps of adding water to the bamboo wood cellulose nanofibers for immersion for 20-30 hours, and then taking out the bamboo wood cellulose nanofibers and continuing to add ethanol solution for immersion for 20-30 hours; Preferably, the pressure and heat treatment step is performed for 6-10 hours.
4. The anti-aging high-grade waterproof asphalt according to any one of claims 1 to 3, characterized in that: The filler includes activated palygorskite; Preferably, the method for preparing the activated palygorskite comprises the steps of adding the palygorskite to dilute hydrochloric acid and mixing, and treating the palygorskite at 50-80° C.; Preferably, the mass concentration of the dilute hydrochloric acid is 1%-2%; Preferably, the mass ratio of the palygorskite to the dilute hydrochloric acid is 1:2-4 g / mL; Preferably, the treatment time is 40-80 min; Preferably, the method further comprises the steps of washing and drying the treated activated palygorskite.
5. The anti-aging high-grade waterproof asphalt according to any one of claims 1 to 4, characterized in that: The base asphalt includes heavy cross-linked 70# asphalt.
6. The anti-aging high-grade waterproof asphalt according to any one of claims 1 to 5, characterized in that: The aromatic content of the catalytic cracking oil slurry is 40%-48%.
7. The anti-aging high-grade waterproof asphalt according to any one of claims 1 to 6, characterized in that: The converting agent includes silicotungstic acid.
8. A method for preparing the anti-aging high-grade waterproof asphalt according to any one of claims 1 to 7, characterized in that: The method comprises the steps of mixing selected amounts of the base asphalt, catalytic slurry, furfural extracted oil, conversion agent, absorbent and filler; Preferably, the temperature of the mixing step is 120°C-130°C.
9. The method for preparing the anti-aging high-grade waterproof asphalt according to claim 8, characterized in that: The steps include: (1) heating a selected amount of the base asphalt to 120° C.-130° C.; (2) continuing to add the selected amount of the catalytic oil slurry and furfural extracted oil, and performing high-speed shearing at a speed of 1000-1500 r / min for 30-40 min; (3) continuing to add the selected amount of the conversion agent and absorbent, and continuing shearing for 20-40 minutes, and then continuing shearing under ultrasonic conditions for 0.5-1 hour; (4) Continue to add the selected amount of the filler and continue shearing for 20-40 minutes.
10. The method for preparing the anti-aging high-grade waterproof asphalt according to claim 9, characterized in that: In the step (3), the power of the ultrasonic step is 4-8W, and the ultrasonic time is 0.5-1h.